2022
DOI: 10.1172/jci.insight.159930
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 inhibition enhances Yes-associated protein–mediated liver regeneration in murine partial hepatectomy models

Abstract: Disrupted liver regeneration following hepatectomy represents an "undruggable" clinical challenge associated with poor patient outcomes. Yes-associated protein (YAP), a transcriptional co-activator which is repressed by the Hippo pathway, is instrumental in liver regeneration. We have previously described an alternative, Hippo-independent, mechanism of YAP activation mediated by tyrosine-protein phosphatase non-receptor type 11 (SHP2) inhibition. Herein, we examined the effects of YAP activation with a selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…5 C). Partial hepatectomy in other murine MASH models has been shown to result in high postoperative mortality ( 4 ). Following partial hepatectomy, mice with diet-induced MASH had a 22.2% survival.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5 C). Partial hepatectomy in other murine MASH models has been shown to result in high postoperative mortality ( 4 ). Following partial hepatectomy, mice with diet-induced MASH had a 22.2% survival.…”
Section: Resultsmentioning
confidence: 99%
“…YAP activation via small molecule inhibitors has been associated with improved liver regeneration in mouse partial hepatectomy models ( 4 , 5 ). In these models the inhibitors have targeted both classic components of the Hippo pathway, which acts as a negative regulator of YAP activity, and alternative YAP activation pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, there is also a loop pathway in the YAP/TAZ‐induced liver regeneration. It has been shown that the binding of YAP/TAZ and TEAD can directly block NR4A1 transcription, while YAP can also stimulate NR4A1 phosphorylation and nuclear translocation under the mediation of AKT, thereby inhibiting the apoptosis‐promoting effect of NR4A1 and promoting hepatocyte proliferation, and the protein tyrosine phosphatase nonreceptor type 11 inhibition amplifies the effect of YAP on NR4A1 385 . NR4A1 can also regulate the ubiquitinated degradation of YAP through a negative feedback mechanism to prevent excessive proliferation of hepatocytes and avoid the occurrence of HCC 386 .…”
Section: Yap/taz and Organ Regenerationmentioning
confidence: 99%